Fluoroquinolone and fortified antibiotics for treating bacterial corneal ulcers. Issue 4 (1st April 2000) - Gangopadhyay, Nibaran; Daniell, Mark; Weih, LeAnn; Taylor, Hugh R
Abstract : AIM: To compare the clinical efficacy of commercially available fluoroquinolone drops with the use of combined fortified antibiotics (tobramycin 1.3%-cefazolin 5%) in treatment of bacterial corneal ulcer. METHODS: The medical records of 140 patients with a diagnosis of bacterial corneal ulcer who were admitted to the Royal Victorian Eye and Ear Hospital, Melbourne, Australia between January 1993 and December 1997 were reviewed retrospectively. Final outcome and results of 138 ulcer episodes were compared between those treated initially with fluoroquinolone and those who received fortified antibiotics. Two patients had been treated with chloramphenicol. RESULTS: No significant treatment difference was found between fluoroquinolone and fortified therapy in terms of final visual outcome. However, serious complications such as corneal perforation, evisceration, or enucleation of the affected eye were more common with fluoroquinolone therapy (16.7%) compared with the fortified therapy (2.4%, p= 0.02). The duration of intensive therapy was less with fluoroquinolone especially in those over 60 years of age (4 days v 6 days, p=0.01). Hospital stay was also less in the fluoroquinolone group compared with the fortified group for all patients and was significantly less with fluoroquinolone treatment (7 days v 10 days, p=0.02) in patients in the age group over 60 years old. CONCLUSIONS: Monotherapy with fluoroquinolone eye drops for the treatment of bacterial corneal ulcers led to shorter duration of intensive therapy and shorter hospital stay compared with combined fortified therapy (tobramycin-cefazolin). This finding may have resulted from quicker clinical response of healing as a result of less toxicity found in the patients treated with fluoroquinolone. However, as some serious complications were encountered more commonly in the fluoroquinolone group, caution should be exercised in using fluoroquinolones in large, deep ulcers in the elderly.